Data on Out-of-school Children in Uganda - (:unkn) unknown (My University, 2019)
Sustainable development goal 4 aims at “inclusive and equitable quality education and lifelong learning opportunities for all”. This implies that no child of school going age should be left out and therefore all efforts have to be mobilised to have all children in school. Sub-Saharan Africa hosts more than half of all out-of-school children. While Uganda implemented Universal Primary Education in 1997 and Universal Secondary Education in 2007, a sizable proportion of children of primary and secondary-school-age are not in school. But results differ according to data sources. What statistics on out of school children do we have for Uganda in the past two decades?
Keywords: African Research